Bacteria and cancer cell pearl chain under dielectrophoresis. Issue 9 (5th February 2021) - Kong, Tian Fook; Tan, Pei Yen; Tay, Benjamin Zikai; Shen, Xinhui; Marcos,
Abstract: In this work, we aim to observe and study the physics of bacteria and cancer cells pearl chain formation under dielectrophoresis (DEP). Experimentally, we visualized the formation of Bacillus subtilis bacterial pearl chain and human breast cancer cell (MCF‐7) chain under positive and negative dielectrophoretic force, respectively. Through a simple simulation with creeping flow, AC/DC electric fields, and particle tracing modules in COMSOL, we examined the mechanism by which bacteria self‐organize into a pearl chain across the gap between two electrodes via DEP. Our simulation results reveal that the region of greatest positive DEP force shifts from the electrode edge to the leading edge of the pearl chain, thus guiding the trajectories of free‐flowing particles toward the leading edge via positive DEP. Our findings additionally highlight the mechanism why the free‐flowing particles are more likely to join the existing pearl chain rather than starting a new pearl chain. This phenomenon is primarily due to the increase in magnitude of electric field gradient, and hence DEP force exerted, with the shortening gap between the pearl chain leading edge and the adjacent electrode. The findings shed light on the observed behavior of preferential pearl chain formation across electrode gaps.